The Legal Contestation Surrounding Female Genital Mutilation in Islamic Boarding Schools: Perspective of Legal Pluralism and its Impact on Women - Fahruddin Ali Sabri; Walida Asitasari (El-Mashlahah, 2025)
This study addressed the gap in understanding among the community in the YY1 Islamic boarding school located in Tuban Regency, Indonesia, about legal pluralism in the practice of Female Genital Mutilation (FGM) between diverse religious, adat, national, and international legal systems. FGM is still perpetuated and socially accepted as a moral, spiritual, and cultural obligation, rather than a violation of women's rights, while national and international regulations continue to regulate the elimination of FGM to promote and protect women's rights. The problem is how women and Islamic boarding schools negotiate and justify their compliance with certain norms in this pluralistic legal environment. This study aims to investigate how individuals navigate the inherent conflict between social norms and individual values related to the protection of women and girls. The study relied on dialogue, observation, and documentation as data collection methods and adopted a legal anthropology approach. The results show that legal pluralism in FGM makes people lean towards the validation of Islamic and adat law as an embodiment of identity and sanctity, so that Islamic law and adat law win the contestation against international human rights law and national law. Their perception of FGM as a harmless practice for women allows for the reconciliation of normative conflicts. Nonetheless, government policies and public education are needed to address the adverse impacts of FGM on women's reproductive health systems.